Osoczowy poziom homocysteiny jako czynnik ryzyka wystąpienia złamań w przebiegu osteoporozy u ludzi w wieku podeszłym = The plasma levels of homocysteine as a risk factor for fractures in osteoporosis in the elderly - Izabela Mirlak; Kamil Radajewski; Natalia Ciesielska; Remigiusz Sokołowski; Marta Podhorecka; Walery Zukow (Kazimierz Wielki University, 2016)
Mirlak Izabela, Radajewski Kamil, Ciesielska Natalia, Sokołowski Remigiusz, Podhorecka Marta, Zukow Walery. Osoczowy poziom homocysteiny jako czynnik ryzyka wystąpienia złamań w przebiegu osteoporozy u ludzi w wieku podeszłym = The plasma levels of homocysteine as a risk factor for fractures in osteoporosis in the elderly. Journal of Education, Health and Sport. 2016;6(4):233-239. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50138 http://ojs.ukw.edu.pl/index.php/johs/article/view/3465   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016.     Osoczowy poziom homocysteiny jako czynnik ryzyka wystąpienia złamań w przebiegu osteoporozy u ludzi w wieku podeszłym The plasma levels of homocysteine as a risk factor for fractures in osteoporosis in the elderly   Izabela Mirlak1, Kamil Radajewski1, Natalia Ciesielska2, Remigiusz Sokołowski3, Marta Podhorecka1, Walery Zukow4   1Sniadecki Specialist Hospital in Nowy Sącz, Poland 2Department and Clinic of Geriatrics, Ludwik Rydygier Collegium Medicum in Bydgoszcz NCU, Poland 3Department of Hygiene, Epidemiology and Ergonomic, Division of Ergonomics and Exercise Physiologym Ludwik Rydygier Collegium Medicum in Bydgoszcz NCU, Poland 4Kazimierz Wielki University, Bydgoszcz, Poland   Słowa kluczowe: osteoporoza, homocysteina, menopauza, złamanie szyjki kości udowej. Keywords: osteoporosis, homocysteine, menopause, hip fracture.   Streszczenie   Wstęp. Osteoporoza jest chorobą charakteryzującą się niską masą kostną i zniszczeniami mikroarchitektury tkanki kostnej, która prowadzi do kruchości kości i zwiększa ryzyko złamań. Osteoporoza i związane z nią złamania kości mają ogromne znaczenie społeczne i gospodarcze na całym świecie. Badania sugerują, że maksymalna masa kostna i szybkość jej utraty związane ze starzeniem, są zdeterminowane przez czynniki genetyczne w podobnym stopniu jak przez czynniki środowiskowe. Kumulacja homocysteiny jest toksyczna dla układu kostnego (osteoporoza), oka (dyslokacja soczewki) i centralnego układu nerwowego (drgawki, zaburzenia psychiatryczne). Wywołuje także zaburzenia układu naczyniowego (udar i inne zdarzenia sercowo naczyniowe). Cel. Wpływ poziomu homocysteiny w osoczu na ryzyko wystąpienia osteoporozy i jej powikłań. Materiały i metody. Posługując się słowami kluczowymi przeszukano zagraniczne bazy bibliograficzne: Embase, Medline, ScienceDirect, Web of Science. Przeanalizowano badania kliniczne, opublikowane w języku angielskim w międzynarodowych czasopismach. Wyniki. Zaobserwowano związek pomiędzy stężeniem homocysteiny, a utratą masy kostnej. Poziom homocysteiny w osoczu jest znacząco wyższy u kobiet z osteoporozą i odwrotnie proporcjonalny do gęstości kości kręgów lędźwiowych i szyjki kości udowej. Wnioski. Osoczowy poziom homocysteiny jest czynnikiem ryzyka wystąpienia złamań w przebiegu osteoporozy u ludzi w wieku podeszłym.   Abstract   Admission. Osteoporosis is a disease characterized by low bone mass and microarchitectural damage of bone tissue  which leads to bone fragility and increased risk of fracture. Osteoporosis and related fractures are of great social and economic importance throughout the world. Studies suggest that the maximum bone mass and the rate of loss associated with aging are determined by genetic factors to a similar as by environmental factors. Accumulation of homocysteine is toxic to the bone (osteoporosis), the eye (the dislocation of the lens), and central nervous system disorders (seizures, psychiatric disorders). Also causes vascular disorders (stroke and other cardiovascular events). Objective. Effect of plasma homocysteine level at risk for osteoporosis and its complications. Systematic review. Materials and methods. Using the keywords searched foreign bibliographic databases: Embase, Medline, ScienceDirect, Web of Science. We analyzed clinical trials published in English in international journals. Results. A correlation between homocysteine and bone loss. Homocysteine levels in plasma are significantly higher in women with osteoporosis and inversely proportional to the bone density of lumbar vertebrae and hip. Conclusions. The plasma levels of homocysteine is a risk factor for fractures in osteoporosis in the elderly.